Study of rolling-sliding contact damage and tribo-chemical behaviour of wheel-rail materials at low temperatures. (April 2022) - Zhou, Liang; Ding, Haohao; Han, Zhenyu; Chen, Chongmu; Liu, Qiyue; Guo, Jun; Wang, Wenjian
Highlights: The wear of wheel and rail materials was studied from 20 °C to −40 °C. The tribo-chemical behaviour of wheel-rail at low temperature was studied. A tribo-film was observed on rail surface after testing at low temperatures. A severe-mild wear transition could be observed with the decrease in temperature. Abstract: The influence of the decrease in environmental temperature on the wear and tribo-chemical behaviours of wheel-rail materials was studied. The results indicated that, at all tested temperatures, a tribo-film zone, oxidation zone and metallic zone were formed on the worn rail surfaces. The decrease in the temperature could decrease the content of O and Fe 3+ ions both in the tribo-film zone and the oxidation zone. As the temperature was reduced below 0 °C, the tribo-film zone on the rail surface enlarged significantly, leading to a decline in the wear rate of the rail material. With the decrease in the temperature, the embedded wear debris spots on the wheel surface increased and the wear rate of wheel decreased gradually. As the temperature declined from 20 °C to −40 °C, the wear form of wheel-rail would transform from the severe wear to mild the wear.